Cultivation of forage cactus genotypes under biosalin agriculture as an alternative to increase forage input from the Brazilian semiarid region: A review (Research, Society and Development, 2021)
In the Brazilian Semiarid Region (BSR), extensive livestock is predominant, where animal feeding is dependent on native vegetation, which due to climatic variability does not meet the needs of herds. To circumvent this problem, the selection of species of forage plants adapted to the Semiarid climate can reduce the impacts caused by climatic adversities on livestock. In this context, a crop that deserves to be highlighted is the forage cactus, which due to its metabolism and morphological characteristics, presents high biomass production, especially in environments with high temperatures and water deficit. To increase the productivity of this crop, given the climatic variability and the conditions of the water resources existing in the BRS, the adoption of agricultural resilience practices, such as biosalin agriculture, can be a viable alternative, providing sustainability to the system. This review aimed to provide an overview of the production capacity of different cactus forage clones grown in a semiarid environment under biosalin agriculture, as a way of increasing the amount of forage to the production systems of this cactus. This review was based on journals available on digital platforms such as ScienceDirect, Scopus, SciELO and Google Scholar, prioritizing articles published in the last 10 years. It was concluded that climate change should affect livestock and that the production system with biosalin agriculture, associated with the best genotypes of forage cactus is a promising alternative for the production of forage in the BRS.